2009
DOI: 10.3357/asem.2236.2009
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Discomfort in Deployed Helicopter Aviators Wearing Body Armor

Abstract: This study provides preliminary evidence that complaints of increased pain frequency during deployment were associated with substantial increases in flight times. Further study is warranted to investigate and confirm the underlying causes of this pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Static posture is tolerable, however, over longer periods movement and changes in sitting angles are necessary to provide periodic rest and optimal physiology of the muscles [5, 6]. Flight related lumbar pain can therefore be caused by posture and muscular fatigue due to extended periods of static positioning [1, 2, 7]. Fatigue and pain are generally alleviated by adjustments of the sitting position, however opportunities for this is restricted in a helicopter seat due to harnesses and body mounted safety gear.…”
Section: Introductionmentioning
confidence: 99%
“…Static posture is tolerable, however, over longer periods movement and changes in sitting angles are necessary to provide periodic rest and optimal physiology of the muscles [5, 6]. Flight related lumbar pain can therefore be caused by posture and muscular fatigue due to extended periods of static positioning [1, 2, 7]. Fatigue and pain are generally alleviated by adjustments of the sitting position, however opportunities for this is restricted in a helicopter seat due to harnesses and body mounted safety gear.…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive epidemiologic evidence pointing to exposure to whole‐body vibration (WBV), especially at near‐resonant low frequencies (4–10 Hz), as a leading risk factor for lower back disorders . Helicopter pilots, in particular, are exposed to vibrations between 3 and 7 Hz, and report increased back and neck pain incidents correlating to the length of the WBV‐exposure . Several epidemiological reviews have shown a strong relationship between human occupational WBV exposure near resonance at 4–6 Hz and likelihood of developing low back pain .…”
mentioning
confidence: 99%
“…American male workers operating vibrating vehicles, such as industrial trucks and tractors, have been reported to have a higher prevalence of low back pain and are three‐times more susceptible to acute herniated lumbar discs than workers whose occupations do not involve such exposures . Also, military helicopter aviators report increased pain during deployment compared to their pre‐deployment reports of pain, with between 22–37% reporting neck and 39–70% reporting low back pain . Further, the frequency of pain was significantly higher for aviators who experienced substantially increased flight hours during deployment compared to those who did not, suggesting that the amount of exposure to WBV may affect the pain .…”
mentioning
confidence: 99%